A vote for Europe? The 2019 EP elections from the voters' perspective - Edgar Grande; Guillem Vidal (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
In this paper we analyze the 2019 EP elections from the voters' perspective. It is based on a novel post-electoral survey covering five North West European countries: Austria, Germany, France, Sweden and the UK. In particular we address the following questions: How important were the lead candidates in the election campaign? Which issues were most important for voters? How do these issues relate to voters' political preferences and ideological orientations? Our findings show that the Spitzenkandidaten process failed to effectively connect European party groups with their voters. Moreover, our analysis reveals that voters had clear issue priorities, which reflected, to a considerable extent, the new cleavage structure which has been shaping party competition in North West European countries in the last two decades.
Keywords: 320; European Union; EP elections; lead candidates; public opinion; cleavages